PREPARATION OF GREEN SAND MOULD (FOUNDRY PRACTICE PART 1) - Sankara Rao, Dr. Lakkoju (Main Workshop, Indian Institute of Technology (BHU), Varanasi, 2016)
This video explains the importance of different tools and step by step procedure to prepare the green sand mold by using single piece wooden pattern.
Keywords: green sand mold; wooden pattern; FOUNDRY PRACTICE; GREEN SAND MOULD